Akuntansi Digital Sebagai Game Changer Bagi Umkm: Solusi Pengelolaan Keuangan di Kota Gorontalo - Abdulrival Hartoyo; Amnatia R Abdullah (Jurnal Literasi Akuntansi, 2025)
Purpose: This study aims to analyze the implementation of digital accounting among micro, small, and medium enterprises (MSMEs) in Gorontalo City, with a focus on the Si APIK application developed by Bank Indonesia Method: The research employed a mixed-methods approach through a quantitative survey of 20 MSME actors and in-depth interviews with MSMEs, Bank Indonesia, and the Cooperative Office. Data were analyzed descriptively to identify adoption levels, challenges, and strategies to strengthen the utilization of digital accounting. Finding: The findings show that 60% of respondents agreed that digital accounting applications help make financial records more systematic, 25% were neutral, and 15% disagreed. The main challenges include limited digital literacy (35%), weak discipline in data entry (30%), poor internet connectivity (20%), and feature incompatibility with small-scale enterprises (15%). Nevertheless, most business actors acknowledged the benefits of digital accounting in improving transparency and access to financing. Novelty: The novelty of this study lies in integrating the analysis of digital accounting adoption with the national policy framework, namely the Presidential Asta Cita, which emphasizes digital transformation and MSME empowerment. This highlights that digital accounting implementation not only supports MSME competitiveness but also aligns with the direction of national digital economic development.